Potassium and Nitrogen Fertilization Effects on Jiggs Bermudagrass Herbage Accumulation, Root–Rhizome Mass, and Tissue Nutrient Concentration. Issue 1 (12th October 2017) - Yarborough, J.K.; Vendramini, J.M.B.; Silveira, M.L.A.; Sollenberger, L.E.; Leon, R.G.; Sanchez, J.M.D.; Leite de Oliveira, F.; Kuhawara, F.; Cecato, U.; Soares Filho, C.V.
Abstract : Core Ideas: Bermudagrass K fertilization affects forage characteristics. Bermudagrass K fertilization effects are influenced by N fertilization. K fertilization is crucial to increase belowground reserves of bermudagrass. Adequate supply of potassium (K) is an important factor that can affect bermudagrass [ Cynodon dactylon (L.) Pers.] production and persistence, particularly in soils with limited nutrient holding capacity. The objectives of this study were to (i) evaluate the effects of different nitrogen (N) and K fertilization strategies on Jiggs bermudagrass herbage accumulation (HA), root–rhizome mass, and K concentration and accumulation in above‐ and belowground tissue; and (ii) identify the critical minimum tissue K concentration below which bermudagrass HA is reduced. The experiment was conducted in a greenhouse at Ona, FL, from August to December, 2014 and 2015. Treatments were a factorial combination of three N (0, 45, and 90 lb/acre) and four K2 O fertilization levels (0, 18, 36, and 72 lb K2 O/acre, the equivalent of 0, 15, 30, and 60 lb K/acre) after every harvest, distributed in a completely randomized design with four replicates. Herbage was harvested every 6 weeks, and root and rhizome mass determined at the end of each year. There were no effects of K fertilization on HA and root–rhizome mass when no N was applied; however, Jiggs HA and root–rhizome biomass increased linearly with increasing K fertilization levels at 45 and 90 lb N/acre. For these N levels, HA increased with tissue K concentration up to 1.4%. Root and rhizome K concentrations decreased linearly with increasing levels of N. Conversely, root–rhizome K content increased with increasing levels of N fertilization. Potassium fertilization increased HA and root–rhizome mass of Jiggs bermudagrass; however, the responses were influenced by N fertilization levels.